Sources of one-word terms used in UK and Lithuanian constitutional law acts - Mockienė, Liudmila; Rackevičienė, Sigita (Taikomoji kalbotyra, 2015)
The article addresses the issues of formation of legal terminology in Lithuanian and English. The terminology of Lithuanian law started to be formed at the beginning of the 20th century. Its development has been influenced by several political upheavals and has undergone considerable changes. Since new legal terms are constantly created, it is worthwhile to compare and contrast Lithuanian term formation tendencies with term formation traditions in other languages. Contrastive research not only reveals peculiarities of term formation in different languages, but allows researchers to see native terminology in a new light and assessing it more objectively. In this article, the Lithuanian constitutional law terms are compared with the English constitutional law terminology that has a long history dating back to the 13th century. The article analyses the sources and means of formation that have been used for the creation of Lithuanian and UK constitutional law terms and reveals important differences in legal term formation in these two languages. The authors expect that the findings of the research will provide useful information to the developers of Lithuanian legal terminology, as well as to the users of Lithuanian and English legal terms.